THE ROLE OF ORGANIZATIONAL LEADERS IN ENCOURAGING TRANSPARENCY AND BUILDING AN ANTI-CORRUPTION CULTURE ON CAMPUS - Dhea Fadilla (ZILLZELL MEDIA PRIMA, 2025)
Corruption is one of the biggest challenges facing organizations in various sectors. Transparency is considered an important principle in preventing corruption. This research aims to determine the role of leaders in encouraging transparency and the strategies used to prevent corruption in organizations. By using a qualitative approach through interviews, this research found that ethical and open leadership can increase a culture of transparency in the work environment. Leaders act as role models in obeying regulations, enforcing anti-corruption policies, and establishing effective monitoring systems. In addition, good leadership has a positive impact in motivating organizational members to behave ethically and report suspected violations. This research suggests the importance of leadership training that focuses on integrity and transparency to create a corruption-free organizational environment.